The Implementation of Q-SETS-Based Physics Teaching Materials Containing Characters to Increase Students' Interest in Learning - Alfiyah, Dewi; Wahyuni, Siti (Physics Communication, 2021)
Good physics teaching materials are teaching materials that present physics concepts that can be understood by students easily and can attract students to read and study physics. However, its implementation is currently not running perfectly. The Q-SETS-based physics teaching materials containing characters are expected to be a solution to encourage students' interest in learning physics, given that interest in learning is an important factor in achieving the success of education. This study intends to analyze the increase in students' interest in learning after using these teaching materials. The method used in this study is an experimental method with students of class X RPL 2 and X MM 3 SMK Negeri 8 Semarang as research subjects. The results of the students' interest in learning before and after being given the Q-SETS-based physics teaching materials containing the characters were 70.08% and 80.51%, respectively. Then, there was a medium category containing an increase in learning interest with an N-gain of 0.35.